2021
DOI: 10.13057/biodiv/d221113
|View full text |Cite
|
Sign up to set email alerts
|

The potential of Nephrolepis biserrata fern as ground cover vegetation in oil palm plantation

Abstract: Abstract. Satriawan H, Fuady Z, Ernawita. 2021. The potential of Nephrolepis biserrata fern as ground cover vegetation in oil palm plantation. Biodiversitas 22: 4808-4817. Nuisance plants or weeds are commonly found in agricultural landscapes including in oil palm plantations. Despite being considered as weeds, several of them have the potential to be used as ground cover vegetation including Nephrolepis biserrata (Sw). Schott. This fern species exhibits beneficial characteristic as ground cover plant especial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Furthermore, Nephrolepis bisserata was the dominant species, where the material deposit had a higher C/N ratio and a more humid environment (Figure 11). Unlike other fern species, it is more tolerant of less fertile growing mediums, as previously described by Saharizan et al (2021) and Satriawan et al (2021).…”
Section: Ch Dd Eg Gv Nb Nbr Nc Pp Ppe Pa Ve Venmentioning
confidence: 62%
“…Furthermore, Nephrolepis bisserata was the dominant species, where the material deposit had a higher C/N ratio and a more humid environment (Figure 11). Unlike other fern species, it is more tolerant of less fertile growing mediums, as previously described by Saharizan et al (2021) and Satriawan et al (2021).…”
Section: Ch Dd Eg Gv Nb Nbr Nc Pp Ppe Pa Ve Venmentioning
confidence: 62%
“…N. biserrata be able to accumulate nitrogen (N) nutrients at 1.23-1.53%, phosphorus (P) at 0.18-0.22%, and potassium (K) at 1.4-1.67% with a total dry biomass of 27.1 tons/ha, carbon (C) accumulation of 0.9 tons/ha/year, and soil carbon stocks between 76.4 -97.4 tons/ha/year (Satriawan et al, 2021). Saputra et al (2023) revealed that the plant density of N. biserrata has a significant impact on the percentage of coverage and the dry weight of oil palm roots, where a denser density produces better microclimate conditions compared to medium or low density.…”
Section: Introductionmentioning
confidence: 99%
“…Several types of pteridophytes can be used as food, traditional medicines, handicrafts, and ornamental plants (Suryana et al 2018). In forest ecosystems, pteridophytes play a role in protecting the soil from erosion, maintaining moisture of the understory vegetation layer, being a litter mixer for the formation of soil nutrients, producers in the food chain, and habitat for some animals (Ridianingsih et al 2017;Satriawan et al 2021). Pteridophytes can also be used as indicators of ecosystem quality and environmental changes (Silva et al 2018) since they have cosmopolitan nature, good adaptation to various environments, and can grow in any area without being introduced or cultivated.…”
Section: Introductionmentioning
confidence: 99%